Risk of recurrent venous thromboembolism after a first oestrogen-associated episode - Gal, Grégoire Le; Kovacs, Michael J.; Carrier, Marc; Do, Kimberley; Kahn, Susan R.; Wells, Philip S.; Anderson, David A.; Chagnon, Isabelle; Solymoss, Susan; Crowther, Mark; Righini, Marc; Lacut, Karine; White, Richard H.; Vickars, Linda; Rodger, Marc (Thrombosis and Haemostasis, 2010)
The use of exogenous oestrogen in women with otherwise unprovoked venous thromboembolism (VTE) could be considered sufficient explanation to classify VTE as provoked if the risk of recurrent VTE after 3–6 months of anticoagulant treatment is similar to the risk of recurrent VTE observed after a surgery or prolonged immobilisation. Our objective was to assess the risk of recurrent VTE in women after a first unprovoked episode on oestrogen. The REVERSE study is a cohort study of patients with a first unprovoked VTE treated with anticoagulant treatment for 5–7 months. The risk of recurrent VTE during follow-up was compared between women users and non users of oestrogen at the time of index VTE. Among the 646 patients included, 314 were women, of them 67 were current users of oestrogen at the time of their VTE: 49 were on oral contraceptives and 18 on post-menopausal hormone replacement therapy (HRT). No significant association was found between oestrogen exposure, either oral contraceptives or HRT, and a lower risk of recurrent VTE after adjustment for age, or analysis restricted to women in the same age range as oestrogen contraceptives and HRT users, respectively. The risk of recurrent VTE is low in women after a first otherwise unprovoked oestrogen-associated VTE. However, this risk is not significantly lower than in women whose VTE was not related to oestrogen use.
Keywords: Venous thromboembolism; recurrence; cohort study; oestrogens